2008
DOI: 10.2165/00002512-200825080-00007
|View full text |Cite
|
Sign up to set email alerts
|

Defining Treatment Response to Donepezil in Alzheimer’s Disease

Abstract: The definition of treatment 'response' in a progressive neurodegenerative disease can encompass a variety of outcomes, including short-term improvement, longer-term stabilization and a slowed decline in one or more clinically relevant symptoms or symptom domains. The ability to identify groups of people who respond to donepezil underscores the clinical utility of the medication and may contribute to more focused assessments of the cost effectiveness of cholinesterase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Current treatments for AD are unable to cure or halt the progress of the disease, and have only mixed results in alleviating the symptoms. The most commonly used medication, Donepezil, shows some benefit for 20%–60% of patients, 1 but a substantial and marked benefit for only 2.3%. 2 However, a long-term study showed no significant benefit compared to placebo for improving daily living functions of Alzheimer’s patients, 3 and many patients discontinue it due to severe side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current treatments for AD are unable to cure or halt the progress of the disease, and have only mixed results in alleviating the symptoms. The most commonly used medication, Donepezil, shows some benefit for 20%–60% of patients, 1 but a substantial and marked benefit for only 2.3%. 2 However, a long-term study showed no significant benefit compared to placebo for improving daily living functions of Alzheimer’s patients, 3 and many patients discontinue it due to severe side effects.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, a long-term study showed no significant benefit compared to placebo for improving daily living functions of Alzheimer’s patients, 3 and many patients discontinue it due to severe side effects. 1 , 2 This study investigates a new protocol on the use of repetitive transcranial magnetic stimulation (rTMS) as a potential treatment for AD. rTMS is a technique that has been successfully used to treat the symptoms of various neurological and psychiatric disorders, including depression, schizophrenia, and Parkinson’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who ‘respond’ to treatment are generally regarded as those who demonstrate a clinically meaningful benefit on an outcome measure. In neurodegenerative diseases, a treatment response refers to short-term improvement, longer-term stabilization or a slowed decline in one or more clinically relevant symptom domains [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the donepezil has been clinically recognized to stabilize cognition for 6 to 12 months, a large proportion of AD patients experience cognitive decline even after the initial intervention. 2 Possibly the reason for these differences in treatment responsiveness are due to various factors such as racial, ethnic, genotype disparities, clinical stage of dementia, co-morbidities, concomitant medication, functional and structural neuronal substrates. 2 3 4 5 However, fundamental reason for this variability is not well understood, but this is essential for understanding etiologies of AD and enhancing effective strategies for management of AD.…”
Section: Introductionmentioning
confidence: 99%